Research on the Construction of Nurses' Core Competence Knowledge Network Based on Computer Mind Mapping. Issue 3 (August 2021) - Tang, Meiling; Gui, Yuanyuan; Liu, Hongmin
Abstract: The core competence of nurses has become the main basis for evaluating the performance of nursing work, which is of great significance in the improvement of nurses' personal quality and the development of nursing profession. This study constructed a core competency evaluation index system based on computer mind maps. After two rounds of index modification, four first-level indicators of theoretical knowledge, professional skills, related abilities, and professional traits were determined, which enriched the structure and evaluation of the core competence elements of nurses. Standard research makes the research results more objective. The results show that the constructed index system is scientific, reliable and highly credible. It has certain practical significance for the training, selection and assessment of registered nurses.